IMPLEMENTATION OF GOOD GOVERNANCE PRINCIPLES IN THE RECRUITMENT AND SELECTION PROCESS OF GOVERNMENT EMPLOYEES IN INDONESIA - Azzahra, Nur Alfia; Ariansyah, Aji Nur; Imawan, Yana Noor; Siddiq, Dedi Muhammad; Ramli, Nur Haslina Binti (International Journal of Social Service and Research, 2024)
Good governance principles are very important in the public sector because they aim to ensure that government institutions work effectively, efficiently, and responsively to the needs and aspirations of the community. Implementing good governance in the public sector not only helps increase efficiency and accountability, but also strengthens democracy and encourages public participation in the decision-making process. This research tries to discuss the extent to which the good governance principles are reflected and implemented in the recruitment and selection of candidates for civil servants. Taking the context of the recruitment and selection process in one of the districts in Indonesia, this research uses a qualitative methodology by collecting data in the form of semi-structured interviews with 25 participants from the recruitment and selection committee and the candidates of civil servants. This research found that overall, the good governance principles are relatively reflected and implemented properly in the in the recruitment and selection of candidates for civil servants although there are some indications of a mismatch between the qualifications of prospective employees and the real needs of the government institution the candidates will work for. This research also found indications of a low level of transparency in the implementation of recruitment and selection, giving rise to opportunities for favoritism and nepotism.